Analisis Fenomena Urban Heat Island (UHI) Multitemporal dengan Google Earth Engine (GEE) Di Kota Semarang - Mariescha Mega Az Zahra; Hasmaulia, Qaanitah; Ash- Shidqi, Muhammad Rafi; Mataburu, Ilham Badaruddin (Jurnal Sains Geografi, 2025)
Climate change is one of the phenomena that is often the main topic of every country. However, since the 19th century, human actions have become the main factor in climate change that triggers various problems, one of which is the Urban Heat Island (UHI). Semarang City is one of the metropolitan cities on Java Island. According to the Central Statistics Agency of Semarang City, in the period 2019-2023, 2019 was the highest year in population growth rate in Semarang City, which was around 1.57 while the population growth rate in 2023 was around 0.9. This study aims to analyze the Urban Heat Island (UHI) phenomenon in Semarang City multitemporally from 2019-2024. The research method used is a quantitative method with a geospatial approach and remote sensing analysis. The data used are the administrative boundaries of Semarang City sub-districts and Landsat 8 Collection 2 satellite imagery obtained from GEE, then the data is processed to obtain a temperature distribution map in Semarang City in 2019-2024. The results show a relatively high frequency of surface temperatures in 2019 and decreased in 2020 to 2021 due to the pandemic and also the suppression of population growth. Temperatures began to rise as community activities resumed after the pandemic and the peak average temperature in 2024 exceeded the average temperature in 2019.